2005
DOI: 10.1590/s1413-78522005000300001
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento da luxação femoro-patelar aguda pelo reparo do ligamento femoro-patelar medial

Abstract: SUMMARYThe authors evaluated the evolution of seventeen patients with acute patellofemoral dislocation. Patients were treated through medial patellar ligament suture. The suture of the ligament was performed by arthroscopy in nine patients with ligament lesion near to the patella. The other eight patients, with patellofemoral ligament lesion occurring near to the femoral epicondyle, were treated by reinsertion at the femoral epicondyle with anchors. The patients had a mean follow-up period of forty months and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…For Steensen et al 18 , this value was found to be 17 mm. According to some authors, 17 , 21 , 24 the femoral insertion is the main location for injuries to the MPFL in cases of acute luxation of the patella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Steensen et al 18 , this value was found to be 17 mm. According to some authors, 17 , 21 , 24 the femoral insertion is the main location for injuries to the MPFL in cases of acute luxation of the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical and biomechanical studies on the MPFL have enabled its repair or reconstruction utilizing different surgical techniques, which has led to improved results in the surgical treatment of acute luxation of the patella. 17 , 18 – 20 However, there are disagreements in the medical community regarding the anatomy of this ligament. 14 The purpose of the present study was to contribute to the knowledge of the anatomy, relationships, and anatomical variations of the MPFL in adult human cadavers.…”
Section: Introductionmentioning
confidence: 99%